Analysis of solid waste from ships and modeling of its generation on the river Danube in Serbia. Issue 6 (June 2013) - Presburger Ulniković, Vladanka; Vukić, Marija; Milutinović-Nikolić, Aleksandra
This study focuses on the issues related to the waste management in river ports in general and, particularly, in ports on the river Danube's flow through Serbia. The ports of Apatin, Bezdan, Backa Palanka, Novi Sad, Belgrade, Smederevo, Veliko Gradiste, Prahovo and Kladovo were analyzed. The input data (number of watercrafts, passengers and crew members) were obtained from harbor authorities for the period 2005–2009. The quantities of solid waste generated on both cruise and cargo ships are considered in this article. As there is no strategy for waste treatment in the ports in Serbia, these data are extremely valuable for further design of equipment for waste treatment and collection. Trends in data were analyzed and regression models were used to predict the waste quantities in each port in next 3 years. The obtained trends could be utilized as the basis for the calculation of the equipment capacities for waste selection, collection, storage and treatment. The results presented in this study establish the need for an organized management system for this type of waste, as well as suggest where the terminals for collection, storage and treatment of solid waste from ships should be located.